On the Analysis of Evolutionary Algorithms - Jansen, Thomas; Wegener, Ingo (Universität Dortmund, 2001)
There is a lot of experimental evidence that crossover is, for some functions, an essential operator of evolutionary algorithms. Nevertheless, it was an open problem to prove for some function that an evolutionary algorithm using crossover is essentially more efficient than evolutionary algorithms without crossover. In this paper, such an example is presented and its properties are proved.
Reihe Computational Intelligence ; 51
Keywords: 004